A case study on the application of new media technology and market expansion of rural enterprises in Central China - Liu, Meng; Wan Abas, Wan Antia; Mamat, Roslina (Redfame Publishing, 2024)
New media has become a critical marketing method in modern times and plays a vital role in rural China's market expansion and development. Currently, the sales of agricultural products by Chinese rural enterprises have become an indispensable part of agricultural product marketing. In the face of fierce market competition, these companies must focus on building agricultural product brands to enhance market competitiveness continuously. However, under the influence of traditional economic concepts and production models, enterprises in some rural areas of China still need to understand brand building, which limits the effective use of new media and results in certain constraints on marketing agricultural products. Therefore, this article aims to conduct an in-depth study of how rural enterprises use new media technology to highlight their products' unique features and advantages by formulating effective marketing promotion strategies.In the face of fierce market competition, rural enterprises need to use creative marketing methods to increase the visibility and recognition of their products. To this end, researchers have proposed marketing promotion strategies through new media technology. In the process of brand building, this article emphasizes the combination of product characteristics and local culture to ensure that the brand image is more in line with the tastes and needs of local consumers. Through innovative designs of brand logos, slogans, etc., rural enterprises are expected to stand out in the market and enhance their competitiveness in new media marketing. Ultimately, this article aims to provide compelling new media marketing strategies for rural enterprises to promote the upgrade of their brand image and improve the market competitiveness of agricultural product sales. Copyright for this article is retained by the author(s).